Ivermectin inhibits epithelial-to-mesenchymal transition via Wnt signaling in endocrine-resistant breast cancer cells. - Kitiya Rujimongkon; Patthamapon Adchariyasakulchai; Phum Meeprasertskul; Wannarasmi Ketchart (PLoS ONE, 2025)
Ivermectin (IVM), an antiparasitic drug, has been explored for its anticancer properties in various cancer types, including breast cancer. Endocrine therapy resistance poses a significant challenge in breast cancer treatment, often leading to metastasis prevention failure. This study aimed to investigate the effects of IVM on endocrine-resistant breast cancer cells, focusing on mechanisms associated with epithelial-to-mesenchymal transition (EMT). IVM was administered to endocrine-resistant breast cancer cell lines, MCF-7/LCC2 (tamoxifen resistant) and MCF-7/LCC9 (fulvestrant resistant), to evaluate its influence on cell proliferation, invasion, and EMT-related mechanisms. The findings indicated that IVM's half-maximum inhibitory concentration (IC50) inhibited MCF-7/LCC2 and MCF-7/LCC9 at 9.35 and 9.06 µM, respectively, within 24 h of treatment. Moreover, IC50 concentration treatment for 24 h led to over a 50% reduction in cell motility and a 62% and 35% decrease in cell invasion in MCF-7/LCC2 and MCF-7/LCC9 cells, respectively. Metastasis biomarkers demonstrated that IVM treatment reduced the expression of vimentin and snail. The study also discovered that IVM diminished the expression of Wnt5a/b and lipoprotein receptor-related protein 6 (LRP6), associated with the metastasis-related Wnt signaling pathway. In conclusion, IVM inhibits the Wnt signaling pathway associated with EMT in the metastasis of endocrine-resistant breast cancer cells. These insights underscore the potential of repurposing IVM for endocrine-resistant breast cancer patients.